What's “New” About New Forms of Organizing? - Puranam, Phanish; Alexy, Oliver; Reitzig, Markus (Academy of Management Review, 2014)
In order to assess whether new theories are necessary to explain new forms of organizing or existing theories suffice, we must first specify exactly what makes a form of organizing “new.” We propose clear criteria for making such an assessment and show how they are useful in assessing if and when new theories of organizing may truly be needed. We illustrate our arguments by contrasting forms of organizing often considered novel, such as Linux, Wikipedia, and Oticon, against their traditional counterparts. We conclude that even when there may be little that existing theory cannot explain about individual elements in these new forms of organizing, opportunities for new theorizing lie in understanding the bundles of co-occurring elements that seem to underlie them and why the same bundles occur in widely disparate organizations.